Doing transformational change in the English NHS in the context of "big bang" redisorganisation: Findings from the North East transformation system. Issue 1 (16th March 2015) - Hunter, David J.; Erskine, Jonathan; Small, Adrian; McGovern, Tom; Hicks, Chris; Whitty, Paula; Lugsden, Edward
Abstract : Purpose: – The purpose of this paper is to examine a bold and ambitious scheme known as the North East transformation system (NETS). The principal aim of the NETS is the achievement of a step-change in the quality of health services delivered to people living in the North East region of England. The paper charts the origins of the NETS and its early journey before describing what happened to it when the UK coalition government published its proposals for unexpected major structural change in the NHS. This had a profound impact on the leadership and direction of the NETS and resulted in it taking a different direction from that intended. Design/methodology/approach: – The research design took the form of a mixed methods, longitudinal 3.5-year study aimed at exploring transformational change in terms of content, context, process and outcomes. The sample of study sites comprised 14 NHS trusts in the North East region chosen to provide geographical coverage of the area and to reflect the scale, scope and variety of the bodies that formed part of the NETS programme. The qualitative component of the research, which the paper draws upon, included 68 semi-structured interviews, observational studies and focus groups. Data analysis made use of both deductive and inductive frameworks. The deductive framework adopted was Pettigrew et al. 's "receptive contexts for change" and four of the eight factors stood out as especially important and form the basis of the paper. Findings: – The fate of the NETS was shaped and influenced by the eight factors comprising the Pettigrew et al. receptive contexts for change framework but four factors in particular stood out as being especially significant: environmental pressure, quality and coherence of policy, key people leading change, supportive organisational culture. Perhaps the most significant lesson from the NETS is that achieving whole systems change is particularly vulnerable to the vicissitudes of politics especially where that system, like the UK NHS, is itself subject to those very same pressures. Yet, despite having an enormous influence on health policy, the political context is frequently avoided in research or not regarded as instrumental in determining the outcomes in respect of transformational change. Research limitations/implications: – The chief limitation is the credibility and authenticity of the interviews captured at particular points in time. These formed the datebase for subsequent analysis. The authors sought to guard against possible bias by supplementing interviews with observational studies and focus groups as well as running two dissemination events at which emerging findings from the study were subjected to independent external scrutiny and comment. These events provided a form of validation for the key study findings. Practical implications: – The research findings demonstrate the importance of context for the likely outcome and success of complex transformational change initiatives. These require time to become embedded and demonstrate results especially when focused on changing culture and behaviour. But, in practice, allowing sufficient time during which the organisation may remain sufficiently stable to allow the change intervention to run its course and become embedded and sustainable is highly problematic. The consequence is that bold and ambitious efforts like the NETS are not given the space and stability to prove themselves. Too often, politics and external environmental pressures intrude in ways that may prove dysfunctional and negative. Social implications: – Unless a different approach to transformational change and its leadership and management is adopted, then changing the NHS to enable it to appear more responsive to changing health care needs and expectations will remain a cause for concern. Ultimately the public will be the losers if the NHS remains insensitive to changing needs and expectations. The patient experience was at the centre of the NETS programme. Originality/value: – The study is original insofar as no other has sought to evaluate the NETS independently and over a reasonable time period. The research design, based on a mixed-methods approach, is unusual in evaluations of this nature. The study's conclusions are not so original but their value lies in largely confirming and reinforcing the findings from other studies. It perhaps goes further in stressing the impact of politics on health policy and the negative consequences of constant organisational change on attempts to achieve deep change in the way the NHS is organised and led.